LEARNING STYLE AND ACADEMIC ACHIEVEMENT OF SCHOOL CHILDREN - AN EXPLORATORY STUDY - G. VIJAYA LAKSHMI; K. AROCKIA MARAICHELVI (The Journal of Research ANGRAU, 2023)
This study explored the interrelationship between Learning Style (LS) and Academic Achievement (AA) of students (11-15 years old) enrolled in schools following the Samacheer Kalvi syllabus (Unified Education Board of the state of Tamil Nadu) among a total of 3026 schoolgoing children from the four zones of Coimbatore in the state of Tamil Nadu during November 2021 to March 2022. A cross-sectional research design was used. Misra’s Learning Style Inventory (LSI) was administered to define the Learning Style of the children. AA was analysed using their yearly report card for five major exams. Subject–wise average marks scored (Tamil, English, Mathematics, Science, and Social Science) were computed and graded. Children’s learning style was found to be significantly associated with all the subjects except the second language (Tamil). The enactive reproducing style had a positive impact on their academic achievement in English, Mathematics, and Science. Verbal constructive style affected their academic achievement negatively. Figural constructive and figural reproducing learning styles were found to have a positive impact on Mathematics, Science, and Social Science.